STUDI AWAL PROSES INAKTIVASI ENZIM LIPOKSIGENASE UNTUK PRODUKSI TEPUNG BIJI KECIPIR SEBAGAI BAHAN BAKU TEPUNG KOMPOSIT - M Endy Y; Dwi H; Fahmi A; Indah H; Erlangga -; Ndaru Okvitarini; Fiqih Putri J (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2010)
Soybean is known as source of protein. Soybean is also rich of nutrition such as minerals, vitamin B, complex carbohydrate and food fiber. Nevertheless central java is still lack of soybean. Winged bean (Psophocarpus tetragonolobus L) which its nutrition content is similar with soybean, is expected as the substitute of  soybean. Winged bean can be used as source of protein by transforming it into composite flour which can be used as food product or edible film in food packaging. The usage of winged bean is limited, such as in tofu production. This is caused by strong bitter beany flavour of winged bean. The beany flavour is caused by the conversion of unsaturated fatty acid especially linoleate that catalyzed by lipoksigenase. In order to avoid the beany flavour, it’s urge to find an appropriate method which able to extract the oil of winged bean in the low or zero activity of lipoksigenase. In order to avoid the conversion of hydroperoxide fatty acid, we need to develop an effective extraction method which inactivate the lipoksigenase and also separate the unsaturated fatty acid in winged bean. This research is used to develop process scheme of winged bean’s oil thermal extraction, so we can produce flour of winged bean which is free of bitter beany flavour. The research was begins by designing and fabricate the enzimatics inactivation extractio, and followed by study the thermal extraction process parameter. The parameters of enzymatic inactivation extraction were ethanol concentration (75 – 95%) and  pH (3-6). The samples of each variable were analyzed by using Ultra Violet Spectrophotometer. The Bio-extractor has been developed with multifunction, which were inactivating the lipoksigenase and extract the oil of winged bean. The higher solvent concentration, the unsaturated fatty acid concentration is lower, but at higher pH, the unsaturated fatty acid concentration is higher also. Keywords: enzyme, flour, inactivation, winged bean